Education policies in pakistan : politics, projections, and practices - Shahid Siddiqui (Pakistan : Oxford University Press, 2016)
This book attempts to critically study the education policies in Pakistan in a holistic manner. The rationale for the education policy and its planning process are discussed in detail. Each theme is tracked through policies set in motion from 1947 up to policy documents presented till the first quarter of 2021.
Includes bibliographical references and Index.
Keywords: Education Pakistan; Education and state Pakistan